Synthesis of hexagonal-symmetry α-iron oxyhydroxide crystals using reduced graphene oxide as a surfactant and their Li storage properties - Lim, Tuti Mariana (2013)
Microcrystalline α-iron oxyhydroxide/reduced graphene oxide (α-FeOOH/rGO) samples have been successfully synthesized by a facile hydrothermal process. The α-FeOOH/rGO samples are either hexagonal disks with a diameter of [similar]1 μm and a thickness of 300 nm or hexapods with a diameter of [similar]2 μm and a thickness of 700 nm, while only bulk and aggregated FeOOH is observed without the addition of graphene oxide sheets. The size and shape of the α-FeOOH depend on the reaction time, concentration of Fe3+, and the addition of graphene oxide. The growth of the hexagonal disks and hexapods is mainly due to a series of phase and structural transformations. The α-FeOOH/rGO displays superior anode performance with a high reversible specific capacity of 569 mA h g−1 at the 50th cycle.